Mapping frailty in people living with HIV: A nationwide study in Greece. Issue 2 (15th July 2022) - Tsakona, Dimitra; Kapetanakis, Anargyros; Kyrou, Dimitrios; Vrontaras, Nikolaos; Xochelli, Aliki; Metallidis, Simeon; Tsachouridou, Olga; Chini, Maria; Meliou, Maria; Psichogiou, Mina; Basoulis, Dimitrios; Antoniadou, Anastasia; et al.
Abstract: Objectives: Frailty is known to affect people living with HIV prematurely, compared to the ageing seronegative population. In this cross‐sectional study, we aimed to assess frailty prevalence in people living with HIV in Greece and find associations of frailty criteria with clinical data. Methods: Demographic and clinical data were collected from 477 participants in six HIV clinics. Fried's frailty phenotype was used to assess frailty prevalence, and participants were classified as frail, pre‐frail or robust. Associations of several factors with overall frailty phenotype, as well as with frailty criteria, were explored. Results: The median age was 43 years old (IQR = 51.5) and 444/477 (93%) were men. Most of the participants (429/477, 93.5%) had an undetectable HIV viral load, and a CD4 cell count over 500 cells/μl (366/477, 76.7%). Frailty assessment classified 285/477 (62.1%) as robust, 155/477 (33.8%) as pre‐frail and 19/477 (4.1%) as frail. Weakness in grip strength was the most prevalent criterion (128/477, 26.8%), followed by exhaustion (46/477, 9.6%). Lower CD4 cell count, history of AIDS diagnosis, CNS disorders, psychiatric diagnoses, and polypharmacy were strongly associated with frailty. Conclusions: Although the prevalence of frailty in people living with HIV in Greece is uncommon, when combined with pre‐frailty over a third of people are affected, which requires attention in clinical practice. The physical and psychological aspects of frailty highlight the need for a holistic approach to prevent or counteract it. The diverse associations of frailty criteria with HIV‐related and non‐HIV‐related factors suggest a possible variation in people's different healthcare needs.